1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Understanding a proof about groups and cosets

  1. Aug 31, 2013 #1
    1. The problem statement, all variables and given/known data
    H is a subgroup of G, and a and b are elements of G.

    Show that Ha=Hb iff [itex] ab^{-1} \in H [/itex] .
    3. The attempt at a solution

    line 1: Then a=1a=hb for some h in H.
    then we multiply both sides by b inverse.
    and we get [itex] ab^{-1}=h [/itex]
    This is a proof in my book.
    My question is on line 1 when they write 1a, is 1 the identity element in H.
    So basically Ha=1a and this trick allows the rest to follow.
     
  2. jcsd
  3. Aug 31, 2013 #2

    CompuChip

    User Avatar
    Science Advisor
    Homework Helper

    H is a subgroup, so the identity in G is also the identity in H.
     
  4. Sep 1, 2013 #3

    CompuChip

    User Avatar
    Science Advisor
    Homework Helper

    Actually my answer was a bit short, so let me expand on it a bit more.

    Recall the definition ##Ha \equiv \{ ha \mid h \in H \}##. Let's consider the '=>' direction first and assume that ##Ha = Hb##. Consider the fixed element ##a##. Since ##e \in H## (I prefer e over 1 to indicate the identity element), ##a = ea \in Ha##. On the other hand, since Ha = Hb, ##a \in Hb## meaning that there exists some ##h \in H## such that ##a = hb##. From this is follows that ##a b^{-1} (= h) \in H## which is all you needed to show.

    I assume that after that they proceed to show the converse, i.e. if ##a b^{-1} \in H## for the given elements ##a, b## then ##Ha = Hb##. I imagine that proof will run along the lines of: assume ##ab^{-1} \in H##, let ##h \in H## be arbitrary, then ##h a = h a (b^{-1} b) = h (a b^{-1}) b## and since H is a subgroup, ##h (ab^{-1})## is the product of two elements in H which is itself in H, so ##h a = h' b## with ##h' ( = h a b^{-1}) \in H##, hence ##Ha \subseteq Hb## - the proof for ##Hb \subseteq Ha## follows similarly.

    [edit]Note that actually ##\forall a, b \in G \left( a, b \in H \implies ab^{-1} \in H \right)## is a necessary and sufficient condition for H to be a subgroup of G. So basically your theorem is "Ha = Hb iff H is a subgroup" or "For subgroups, and subgroups only, all right cosets are equal".
     
    Last edited: Sep 1, 2013
  5. Sep 13, 2013 #4
    ok thanks
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted



Similar Discussions: Understanding a proof about groups and cosets
  1. Proof about a group (Replies: 3)

Loading...